2022
DOI: 10.3390/jcm11133847
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Pubertal Growth-Spurt Parameters in Children and Adolescents in Colombia: Comparison between Low and Moderate Altitudes

Abstract: Context-specific information, including differences in geographical areas, such as distinct altitudes, can be important to explain variations in physical growth. We aimed to compare the estimation of maximum growth velocity and pubertal growth-spurt parameters of children and adolescents living at low and moderate altitudes in Colombia. A cross-sectional study, including a representative cohort of 30.305 (51% boys) children and adolescents aged 1–18 years from Colombia, was performed. The heights were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…However, the pattern observed in moderate and high-altitude children and adolescents from Colombia 15 and Peru 14 are similar to those reported in this study. This behavior could be characterized as typical of these regions, where girls reached PHV 3 years earlier than boys and not two years as has been described in the literature.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, the pattern observed in moderate and high-altitude children and adolescents from Colombia 15 and Peru 14 are similar to those reported in this study. This behavior could be characterized as typical of these regions, where girls reached PHV 3 years earlier than boys and not two years as has been described in the literature.…”
Section: Discussionsupporting
confidence: 90%
“… 22 , 23 However, this wide difference in years verified in this study coincides with that reported in some recent studies carried out at moderate altitudes in Colombia. 15 As well as at high altitude in Peru, investigating in the province of Huancayo, specifically in the department of Junín (Peru). 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, other factors that could affect the maturity process include altitude. A study from Colombia reported no significant differences in APHV, PHV, and estimated final height between the children and adolescents living at low and moderate altitudes ( 65 ). On the other hand, Peruvian children and adolescents living at different altitudes showed differential timing and tempo of growth; individuals living at sea level experienced an earlier APHV, were taller at APHV, had a higher PHV, and had a taller estimated final height compared to peers living at higher altitudes ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…В этом и многочисленных последующих трудах [Tanner et al, 1966[Tanner et al, , 1976Tanner, Cameron, 1980;Tanner, 1981Tanner, , 1988Tanner, Davies, 1985] Таннер всесторонне разрабатывает многие аспекты роста в подростковом и других возрастах и анализирует взаимные связи соматических, физиологических, эндокринологических, моторных, ментальных показателей в их динамике. В современной мировой литературе феномен пика скорости роста обсуждается в целом ряде контекстов: в связи со скелетной и половой зрелостью [Iuliano-Burns et al, 2001;Molinari et al, 2013;Gasser et al, 2013;Cole et al, 2014]; экологическими особенностями ниши развития популяции, в том числе высотой над уровнем моря [Dabas et al, 2018;Santos et al, 2019;Correa-Rodríguez et al, 2022;Kleanthous et al, 2022]; межгрупповой изменчивостью телосложения и ожирением [Aksglaede et al, 2009;Yokoya, Higuchi, 2014;Narchi et al, 2021]; секулярными трендами [Ali et al, 2001;Aksglaede et al, 2008;Gomula et al, 2021].…”
Section: ключевые слова: антропологическая изменчивость средовые возд...unclassified